Elucidating adolescent aspirational models for the design of public mental health interventions: a mixed-method study in rural Nepal - Sauharda Rai; Safar Bikram Adhikari; Nanda Raj Acharya; Bonnie N. Kaiser; Brandon A. Kohrt (Child and Adolescent Psychiatry and Mental Health, 2017)
Abstract Background Adolescent aspirational models are sets of preferences for an idealized self. Aspirational models influence behavior and exposure to risk factors that shape adult mental and physical health. Cross-cultural understandings of adolescent aspirational models are crucial for successful global mental health programs. The study objective was elucidating adolescent aspirational models to inform interventions in Nepal. Methods Twenty qualitative life trajectory interviews were conducted among adolescents, teachers, and parents. Card sorting (rating and ranking activities) were administered to 72 adolescents aged 15–19 years, stratified by caste/ethnicity: upper caste Brahman and Chhetri, occupational caste Dalit, and ethnic minority Janajati. Results Themes included qualities of an ideal person; life goals, barriers, and resources; emotions and coping; and causes of interpersonal violence, harmful alcohol use, and suicide. Education was the highest valued attribute of ideal persons. Educational attainment received higher prioritization by marginalized social groups (Dalit and Janajati). Poverty was the greatest barrier to achieving life goals. The most common distressing emotion was ‘tension’, which girls endorsed more frequently than boys. Sharing emotions and self-consoling were common responses to distress. Tension was the most common reason for alcohol use, especially among girls. Domestic violence, romantic break-ups, and academic pressure were reasons for suicidality. Conclusion Inability to achieve aspirational models due to a range of barriers was associated with negative emotions—notably tension—and dysfunctional coping that exacerbates barriers, which ultimately results in the triad of interpersonal violence, substance abuse, and suicidality. Interventions should be framed as reducing the locally salient idiom of distress tension and target this triad of threats. Regarding intervention content, youth-endorsed coping mechanisms should be fortified to counter this distress pathway.